Patients' and clinicians' experiences of the DSM-5 Cultural Formulation Interview: A mixed method study in a Swedish outpatient setting. (August 2020) - Wallin, Malin Idar; Dahlin, Marie; Nevonen, Lauri; Bäärnhielm, Sofie
This study is an evaluation of clinicians' and patients' experiences of the core Cultural Formulation Interview (CFI) in DSM-5. The CFI provides a framework for gathering culturally relevant information, but its final form has not been sufficiently evaluated. Aims were to assess the Clinical Utility (CU), Feasibility (F) and Acceptability (A) of the CFI for clinicians and patients, and to explore clinicians' experiences of using the CFI in a multicultural clinical setting in Sweden. A mixed-method design was applied, using the CFI Debriefing Instrument for Clinicians ( N  = 15) and a revised version of the Debriefing Instrument for Patients ( N  = 114) (DIC and DIP, scored from −2 to 2). Focus group interviews were conducted with clinicians. For patients (response rate 50%), the CU mean was 0.98 ( SD  = 0.93) and F mean 1.07 ( SD  = 0.83). Overall rating of the interview was 8.30 ( SD  = 1.75) on a scale from 0 and 10. For clinicians (response rate 94%), the CU mean was 1.14 ( SD  = 0.52), F 0.58 ( SD  = 0.93) and A 1.42 ( SD  = 0.44). From clinician focus-group interviews, the following themes were identified: approaching the patient and the problem in a new manner; co-creating rapport and understanding; and affecting clinical reasoning and assessment. Patients and clinicians found the CFI in DSM-5 to be a feasible, acceptable, and clinically useful assessment tool. The focus group interviews suggested that using the CFI at initial contact can help make psychiatric assessment patient-centred by facilitating patients' illness narratives. We argue for further refinements of the CFI.